2022
DOI: 10.3389/fneur.2022.1001609
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent stroke risk in intracranial atherosclerotic disease

Abstract: Recurrent stroke risk secondary to intracranial atherosclerotic disease remains high despite aggressive medical treatment. This risk is further amplified in subgroups possessing biomarkers of hemodynamic insufficiency and potential for embolization, which have been shown to be independently and synergistically predictive of recurrent stroke. Luminal stenosis was predominantly used as entry criteria in major treatment trials, discounting the potential role of hemodynamics from primary analyses, limiting the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…[2][3][4][5] Recurrent stroke rates, however, remain high, and likely substantially higher in patients with markers of hemodynamic insufficiency. 7,13,[19][20][21] Furthermore, there appears to be a positive relationship between hemodynamic markers in predicting recurrent stroke risk, 19 as the presence of multiple imperfect markers likely increases the probability of a hemodynamically compromised state. This is likely due to the inherent limitations of our current imaging (QMRA, perfusion studies, infarction patterns), since none of these unimodal imaging modalities fully reflect the complex hemodynamic environment surrounding atherosclerotic lesions as each imaging modality likely depicts a piece of the complicated hemodynamic picture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4][5] Recurrent stroke rates, however, remain high, and likely substantially higher in patients with markers of hemodynamic insufficiency. 7,13,[19][20][21] Furthermore, there appears to be a positive relationship between hemodynamic markers in predicting recurrent stroke risk, 19 as the presence of multiple imperfect markers likely increases the probability of a hemodynamically compromised state. This is likely due to the inherent limitations of our current imaging (QMRA, perfusion studies, infarction patterns), since none of these unimodal imaging modalities fully reflect the complex hemodynamic environment surrounding atherosclerotic lesions as each imaging modality likely depicts a piece of the complicated hemodynamic picture.…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial atherosclerotic disease is the leading cause of stroke worldwide 1 with high recurrent stroke rates despite aggressive medical therapies. [2][3][4][5] Challenges in stroke prevention have been attributed to the heterogeneity of disease 6,7 as multiple interrelated stroke mechanisms exist, such as thromboembolism, hypoperfusion, and branch atheromatous disease. [8][9][10] Despite the complexity of stroke mechanisms, randomized treatment trials have focused primarily on luminal stenosis as entry criteria, [2][3][4][5] discounting the potential role of hemodynamics, plaque morphology, and potential for embolization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on carotid plaques showed that the hyperintensity of the T1WI often represented IPH or lipid nucleation, which increased the risk of plaque rupture and the occurrence of arterial embolism resulting in stroke recurrence. Plaque enhancement is a reliable imaging biomarker [ 3 , 44 ]. The degree of plaque enhancement may reflect the level of inflammatory activity caused by increased endothelial permeability and new blood vessels [ 46 ].…”
Section: Hrmri Of Intracranial Atherosclerotic Diseasementioning
confidence: 99%
“…The degree of luminal stenosis in the head and carotid arteries has been considered the traditional measure of the severity of atherosclerotic disease. However, recent evidence has shown that this criterion alone may not accurately assess the risk of adverse events associated with vulnerable plaques [ 3 ]. Therefore, component analysis of atherosclerosis has been utilized to evaluate the extent and mechanism of stenosis and predict the recurrence of ischemic events such as stroke and transient ischemic attack.…”
Section: Introductionmentioning
confidence: 99%